Tandem fusion of hepatitis B core antigen allows assembly of virus-like particles in bacteria and plants with enhanced capacity to accommodate foreign proteins. - Hadrien Peyret; Annick Gehin; Eva C Thuenemann; Donatienne Blond; Aadil El Turabi; Lucy Beales; Dean Clarke; Robert J C Gilbert; Elizabeth E Fry; David I Stuart; Kris Holmes; Nicola J Stonehouse; et al. (PLoS ONE)
The core protein of the hepatitis B virus, HBcAg, assembles into highly immunogenic virus-like particles (HBc VLPs) when expressed in a variety of heterologous systems. Specifically, the major insertion region (MIR) on the HBcAg protein allows the insertion of foreign sequences, which are then exposed on the tips of surface spike structures on the outside of the assembled particle. Here, we present a novel strategy which aids the display of whole proteins on the surface of HBc particles. This strategy, named tandem core, is based on the production of the HBcAg dimer as a single polypeptide chain by tandem fusion of two HBcAg open reading frames. This allows the insertion of large heterologous sequences in only one of the two MIRs in each spike, without compromising VLP formation. We present the use of tandem core technology in both plant and bacterial expression systems. The results show that tandem core particles can be produced with unmodified MIRs, or with one MIR in each tandem dimer modified to contain the entire sequence of GFP or of a camelid nanobody. Both inserted proteins are correctly folded and the nanobody fused to the surface of the tandem core particle (which we name tandibody) retains the ability to bind to its cognate antigen. This technology paves the way for the display of natively folded proteins on the surface of HBc particles either through direct fusion or through non-covalent attachment via a nanobody.